2013
DOI: 10.1021/jm4009828
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship Study of Indole-2-carboxamides Identifies a Potent Allosteric Modulator for the Cannabinoid Receptor 1 (CB1)

Abstract: The cannabinoid CB1 receptor is involved in complex physiological functions. The discovery of CB1 allosteric modulators generates new opportunities for drug discovery targeting the pharmacologically important CB1 receptor. 5-chloro-3-ethyl-N-(4-(piperidin-1-yl)phenethyl)-1H-indole-2-carboxamide (ORG27569; 1) represents a new class of indole-2-carboxamides that exhibit allostery of CB1. To better understand the SAR, a group of indole-2-carboxamide analogs were synthesized and assessed for allostery of the CB1 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(92 citation statements)
references
References 32 publications
(142 reference statements)
3
89
0
Order By: Relevance
“…29 Reduction of 9 by triethylsilane in trifluoroacetic acid at room temperature gave 10 which was hydrolyzed in aqueous sodium hydroxide and ethanol to furnish the intermediate 11 . 26, 27 Amide coupling between 11 and 4- or 3-nitrophenylethylamine in the presence of BOP provided 12 and 13 which were reduced by Raney nickel-catalyzed transfer hydrogenation using hydrazine in ethanol at 50 °C to give 14 and 15 . Reductive amination of amines 14 and 15 with the corresponding aldehydes provided the target compounds 16 - 20 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Reduction of 9 by triethylsilane in trifluoroacetic acid at room temperature gave 10 which was hydrolyzed in aqueous sodium hydroxide and ethanol to furnish the intermediate 11 . 26, 27 Amide coupling between 11 and 4- or 3-nitrophenylethylamine in the presence of BOP provided 12 and 13 which were reduced by Raney nickel-catalyzed transfer hydrogenation using hydrazine in ethanol at 50 °C to give 14 and 15 . Reductive amination of amines 14 and 15 with the corresponding aldehydes provided the target compounds 16 - 20 .…”
Section: Methodsmentioning
confidence: 99%
“…25 Subsequent work found that longer alkyl side chains with up to 9 carbon units at the C3 position of indole ring A could retain activity, whereas linkers other than an ethylene between the amide bond and the phenyl ring B resulted in total loss of activity. 26-28 In an attempt to expand our understanding of the structure-activity relationship on this scaffold, we have designed additional analogs by (i) exploring different substituents at the 4-, 3-, 2-positions of the phenyl ring B, (ii) examining several rigid cyclic ring linkers between the phenyl and the indole rings, and (iii) investigating the effects of shorter alkyl side chain at the C3 position and halogenations at the C5 position of the indole ring A. Here, we report the synthesis of these 1H-indole-2-carboxamide analogs and the evaluation of CB1 and CB2 activities in fluorometric imaging plate reader (FLIPR) based calcium mobilization assays.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained photophore-bearing ethanamines 12, 16 and 22 were then employed in the synthesis of corresponding indole-2-carboxamides 26–29 through the methods (Scheme 2) as we described earlier[32]. The required indole-2-carboxylic acids 23–25 were prepared according to our previous report [33].…”
Section: Chemistrymentioning
confidence: 99%
“…7–9 , Figure 2) reported previously [3133]. Compounds 7 [31], 8 [33] and 9 [32, 35] have been demonstrated to have either comparable or improved allosteric effects to 1 [3133]. Therefore, they were selected along with 1 as the parent compounds to introduce photoactivatable functionalities.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation